Identification of Morphological Characters and Time of Mitotic Musa Paradisiaca cv. Haji - Rina Kurnianingsih; Siti Rosidah; Dinda Sekar Ayu; Eka S Prasedya; Sri Puji Astuti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Musa paradisiaca cv Haji is a local banana of Lombok that has a longer shelf life. The determination of the haji banana genome still uses a scoring method based on morphological character. Clarification of ploidy levels and genome types can be done using chromosome analysis. The initial information needed to perform the karyotype analysis is identifying the cleavage time of M. paradisiaca cv Haji. Banana Haji on the island of Lombok has a different local name, so morphological identification of the haji banana accession is required. Morphological observations were conducted on three accessions of Haji bananas from different cultivation sites. Identification of the time of mitosis cleavage is made by the Squash method. The results showed a uniform synapomorphic character in the haji banana accession. The characters include the aspects of pseudostem (normal), shiny pseudostem, imbricate young bractea (young bractea slightly stacked), red inner bractea, straight ovary, and no pigmentation on the stylus. The autapomorphic character of Haji banana accession in this study included inside the pseudostem of the red-green, the position of horizontal fruit bunches, a fair amount of wax on the surface of the lower leaf, and the petiole of the lower leaf in pink. There are morphological character differences in Haji cultivar accession on pseudostem color and tepal color pigmentation. The time of mitosis division in Haji bananas, especially the prophase stage - metaphase from 06.38 - 07.38 Wita. The results obtained in this study can be used as a foundation to conduct karyotype analysis of Musa paradisisaca cv Haji.ÃÂ